UPACARA NILAPATI SEBUAH INVESTASI RITUAL MENUJU KESELAMATAN DUNIA DAN AKHIRAT (Studi Kasus pada Warga Pasek) - Anak Agung Ayu Alit Widyawati; Mery Ambarnuari (UHN IGB Sugriwa Denpasar, 2022)
The nilapati ceremony is carried out with the aim of purifying the ancestral spirits. This ceremony is carried out based on a reference to the Lebur Sangsa lontar and is carried out as a series with the Ngalinggihang Dewa Hyang ceremony or Dewa Pitara Pratistha. This ceremony is carried out before the Ngalinggihang ceremony. If string with the Pujawali or Piodalan ceremony at Sanggah Pamrajan, the Nilapati Ceremony is carried out after Piodalan, precisely before Nyineb. Based on this, the Nilapati Ceremony is still classified as a Pitra Yadnya ceremony. Considering the implementation is carried out after the Atma Wedana ceremony before Ngalinggihang Dewa Hyang. But if it is carried out after Piodalan before Nyineb, this ceremony belongs to Dewa Yadnya. Nilapati is an atonement ceremony for various sins committed during life and sins due to death which are considered unnatural, namely starch mistakes and starch acts. As for theological factors, sociological factors, and educational factors behind the implementation of the Nilapati ceremony. The Nilapati ceremony, when associated with a cultural form, is a form of materialization of the idea of ​​liberation theology and visualization of the guidelines that direct Hindus to achieve liberation. In addition, the Nīlapati ceremony is an expression of a sign system, so based on semiotic theory this ceremony can be analyzed in the form of verbal signs in the form of puja-stava which must be recited by Pandita when completing the ceremony, and nonverbal semiotics in the form of rituals/bantens that must be offered. The nilapati ceremony contains the meaning of debt redemption (redemption of ancestral debts and debt redemption of the ceremony organizer), purification, and rescue.